ANALISIS PENGARUH KINERJA DENGAN KONSEP KONVENSIONAL DAN KONSEP VALUE BASED TERHADAP RETURN SAHAM (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI PERIODE 2017-2020) - Lutvi Ahmad Ardiansah; Abdul Wahid Mahsuni; Hariri Hariri (Universitas Islam Malang, 2022)
This study aims to determine performance analysis with conventional concepts and value-based concepts in stock returns. The population in this study are manufacturing companies in the basic and chemical industry sectors listed on the Indonesian stock exchange for the period 2017-2020. The sampling technique is purposive sampling technique, the selected sample is 22 companies. The data was taken using the documentation method. The data analysis method used is multiple regression analysis with SPSS software version 14 (Product Statistics and Solution services version 14). The test data used are the simultaneous hypothesis test (f), the coefficient of determination (R2), and the partial hypothesis test (t). The results showed that simultaneously the independent variables did not have a positive effect on the dependent variable. Based on the results of the coefficient of determination, the Adjusted R value was 9.3% while the remaining 90.7% was influenced by other variables not included in this study. Based on the partial test results that return on investment, return on equity, operating cash flow and economic value added do not have a positive effect on stock returns.Keywords : Return On Investment, Return on Equity, Operating Cash Flow, Economic Value Added and Stock Return.